ANALYSIS OF COFFEE STORE IN JAKARTA USING THE WASTE OF COFFEE TO CREATE A CREATIVE INDUSTRY - Prabawanti, Benedicta Evienia; Hapsari, Sri; Silalahi, Engelbertha E (Penerbit Atma Jaya Catholic University of Indonesia, 2020)
Coffee pulp waste is one of the most significant industrial wastes today because, for the last three years, the coffee business has multiplied in Indonesia, especially in urban areas. Coffee pulp waste has economic value if it can use it. This study is (1) to describe the condition of the existing coffee shop in South Jakarta, (2) to find out the social business strategy for the development of the creative industries in the coffee shop by utilizing coffee grounds waste. This study is a qualitative descriptive with a case study approach. To determine the condition of the coffee shop, data was collected through interviews with 30 coffee shop owners in South Jakarta and observation. The SBMC analysis will continue to project the coffee pulp business as a social business. The results showed a coffee shop in South Jakarta produces coffee waste per day 1-5 kg. All owners have not utilized the coffee grounds waste. Through SMBC analysis, education is needed to the coffee shop owner as a supplier of coffee waste and open employment for the community who will recycle coffee grounds into cosmetics. This study concluded that the utilization of coffee waste could create a creative cosmetics industry while overcoming unemployment.